Bacterial regulatory networks: from self-organizing molecules to cell shape and patterns in bacterial communities - Hengge, Regine; Sourjik, Victor (EMBO reports, 2013)
The ESF?EMBO Conference on ?Bacterial Networks? (BacNet13) was held in March 2013, in Pultusk, Poland. It brought together 164 molecular microbiologists, bacterial systems biologists and synthetic biologists to discuss the architecture, function and dynamics of regulatory networks in bacteria.
Gesehen am 09.04.2021